2018
DOI: 10.3390/su10051313
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Local Food: Testing an Extended Norm Taxonomy

Abstract: Consumer attitudes toward consuming and buying locally produced food are well studied. By contrast, the topic of consumer preferences for local food, with a special emphasis on the role of norms, still lacks empirical evidence. To study the influence of norms and morals on the intention to buy local food products, a quantitative study (N = 327) focusing on external social and internalized moral norms was conducted using the constructs of the theory of planned behavior in combination with an extended norm taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 60 publications
1
31
1
Order By: Relevance
“…Third, policy makers should pay particular attention to activating personal norms that were found to be associated with flood risk preparedness (as indicated by the strong correlation of personal norms with investments in flood preparedness in Figure 8). These results are in line with Wenzig and Gruchmann (2018), who showed that personal norms generally have a much larger influence on proenvironmental behavior than social norms, and with Botzen et al (2019b), who showed that personal norms matter more than social norms in a flood risk context. Schwartz (2012) argued that norms need to be activated to be able to influence intention or behavior by being aware of the consequences of actions and feeling responsible.…”
Section: Discussionsupporting
confidence: 90%
“…Third, policy makers should pay particular attention to activating personal norms that were found to be associated with flood risk preparedness (as indicated by the strong correlation of personal norms with investments in flood preparedness in Figure 8). These results are in line with Wenzig and Gruchmann (2018), who showed that personal norms generally have a much larger influence on proenvironmental behavior than social norms, and with Botzen et al (2019b), who showed that personal norms matter more than social norms in a flood risk context. Schwartz (2012) argued that norms need to be activated to be able to influence intention or behavior by being aware of the consequences of actions and feeling responsible.…”
Section: Discussionsupporting
confidence: 90%
“…While in the research conducted by Wenzing and Gruchmann [58], who studied preferences of consumers vis-à-vis local food, (327 respondents took part in the research) the researchers demonstrated that respondents have some limitations when it comes to buying local food that are related to lack of knowledge in this area.…”
Section: Description Of Research Topics and Research Results In The Amentioning
confidence: 99%
“…This technique is widely used by researchers to observe the variables that characterise consumer behaviour [65,[71][72][73][74][75][76][77][78][79][80][81][82].…”
Section: Methodological Approachmentioning
confidence: 99%
“…After performing MCA, a hierarchical cluster analysis (HCA) was conducted for validation [69,70]. In the HCA, a hierarchical grouping was performed then optimised with K-means clustering [76,78]. The analyses were performed using IBM SPSS Statistics (version 20).…”
Section: Methodological Approachmentioning
confidence: 99%